Reification, or, The anxiety of late capitalism - Bewes, Timothy (Verso, 2002)
Reification is the process by which an intangible idea is transformed into an identifiable "thing". This book opens up a new formulation of the theory, claiming that, in this age of late capitalism, reification itself is inseparable from the anxiety people feel towards it.